The FoMO Phenomenon: Impact on Investment Intentions in Millennial Generation with Financial Literacy as Moderation - Nyimas Dewi Murnila Saputri; Agung Putra Raneo; Fida Muthia (Politeknik Ganesha Medan, 2023)
The millennial generation is in a period of various financial activities including investments that require better financial decisions, but the millennial generation is facing modern lifestyle challenges, one of which is the Fear of Missing Out (FoMO). In addition, the fear of the Covid-19 outbreak at the beginning of the pandemic caused negative sentiment for investors. Therefore, it is necessary to look at the role of financial literacy as the basis of strength that can be used as a person's skills and abilities in managing their financial resources effectively. The purpose of this study is to prove and explain the effect of the FoMO phenomenon on investment intention with financial literacy as a moderating variable. This study uses a survey method, namely an online survey with a data analysis method using Moderated Regression Analysis. The sample of this research is the millennial generation who have investments in various financial products. The criteria for this research sample are the millennial generation with an age range of 22-41 years. From the results of the tests carried out, it is known that the financial literacy variable can weaken the influence of FoMO on Investment Intention which is indicated by a significant negative sign and can also be an independent variable that affects Investment Intention